Hypertension and cognitive impairment among older persons in rural Northern Uganda: a cross-sectional study - Joel Oyugi; Jonathan Izudi; Francis Bajunirwe (BMC Geriatrics)
Abstract Background Hypertension is common among older adults and negatively affects cognitive function. Available data on this association is mostly from resource-rich settings and has been understudied in resource-limited settings especially rural areas where the majority of older persons live. We examined the association between hypertension and cognitive impairment in older persons in Kole, a rural district in Uganda, and examined whether sex modifies the association. Methods We conducted a community-based cross-sectional study among older persons aged ≥ 60 years in rural northern Uganda, using a multi-stage sampling approach. The primary exposure was hypertension measured by systolic (≥ 140 mmHg) or diastolic blood pressure (≥ 90 mmHg), or being on anti-hypertensive medication. The dichotomous outcome was cognitive impairment determined by Montreal Cognitive Assessment scores < 26. We used the modified Poisson regression with robust standard errors for the analysis, applying a 5% significance level. Results We studied 420 participants and found 288 (68.6%) had hypertension while 213 (50.7%) had some cognitive impairment. The overall mean age was 68.4 ± 7.2 years, the mean systolic blood pressure was 138.1 ± 23.1 mmHg while diastolic blood pressure was 85.4 ± 11.9 mmHg, and the mean MOCA score was 17.6 ± 7.2. Hypertension was associated with cognitive impairment (adjusted prevalence risk [aPR] 1.26, 95% CI 1.01–1.57), with 4–5 people in the household (aPR 0.80, 95% CI 0.64–0.99), no smoking history (aPR 0.57, 95% CI 0.43–0.76), and dissatisfaction with one’s health (aPR 1.68, 95% CI 1.27–2.21) and satisfaction with the ability to perform usual domestic duties (aPR 0.74, 95% CI 0.55–0.99) being associated. In a sex-stratified analysis, men with hypertension were more likely to experience cognitive impairment (aPR 2.13, 95% CI 1.33–3.40), compared to those with normal blood pressure but there was no significant association among women (aPR 0.97, 95% CI 0.96–1.24). Conclusion Older persons with hypertension were more likely to experience cognitive impairment than those without. In a sex stratied analysis, this observation persists among men but disappears among women. Our results suggest a need to raise awareness and consider regular blood pressure measurement and control in older adults. We recommend longitudinal studies to examine temporality and suggest blood pressure interventions to prevent cognitive impairment in older age.